2022
DOI: 10.1155/2022/8446170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Significance of Antinuclear Antibodies in Biopsy-Proven Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: Aim. Associations between antinuclear antibodies (ANAs) and disease severity in nonalcoholic fatty liver disease (NAFLD) remain unclear. This study aimed to provide reliable estimates of ANA prevalence in subjects with biopsy-proven NAFLD and to investigate whether its associations with liver disease severity were established. Methods. Observational studies measuring ANA in NAFLD patients were derived from the PubMed, Embase, and Web of Science databases from inception to March 30, 2022. The effect size was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…These atrisk patients exhibit higher expression of heavy-chain immunoglobulins and varying gene usage of lightchain immunoglobulins κ and λ. Altered antibody repertoires may arise from aberrant deposition and maturation of intrahepatic B cells into plasma cells during the onset of steatohepatitis 45,46 . Additionally, a subset of MASLD patients have elevated levels of auto-reactive antibodies, which may increase the risk of hepatic damage and fibrosis 47,48 . Given the lack of reliable screening methods to identify MASL patients at risk for developing MASH in clinical settings, dysregulated antibody repertoires can serve as potential markers to stratify these high-risk patients who may require more proactive management.…”
Section: Discussionmentioning
confidence: 99%
“…These atrisk patients exhibit higher expression of heavy-chain immunoglobulins and varying gene usage of lightchain immunoglobulins κ and λ. Altered antibody repertoires may arise from aberrant deposition and maturation of intrahepatic B cells into plasma cells during the onset of steatohepatitis 45,46 . Additionally, a subset of MASLD patients have elevated levels of auto-reactive antibodies, which may increase the risk of hepatic damage and fibrosis 47,48 . Given the lack of reliable screening methods to identify MASL patients at risk for developing MASH in clinical settings, dysregulated antibody repertoires can serve as potential markers to stratify these high-risk patients who may require more proactive management.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, rare autoimmune hepatitis (AIH) may coexist or develop with NAFLD [ 3 ]. A recent systematic review and meta-analysis reported that serum antinuclear antibodies (ANAs) can be detected only in approximately one-quarter of subjects with biopsy-proven NAFLD, but it can confer a greater risk of significant fibrosis only in Eastern populations [ 54 ].…”
Section: Autoantibodies and Nafldmentioning
confidence: 99%
“…На втором этапе осуществляются подтверждающие и дополнительные иммунодиагностические тесты второй линии для выявления специфических печеночных аутоантител в сыворотке крови: 1) АМА-М2, антител к F-актину, LKM-1, LKM- АNА, к которым относится множество органонеспецифических аутоантител, реагирующих с различными антигенами клеточного ядра и цитоплазмы, занимают центральное место в диагностике АИГ-1 и других АИЗП. Частота обнаружения ANA в сыворотках больных АИГ-1 (50-80%) значительно выше, чем у пациентов с ПСХ (39%), неалкогольной жировой болезнью печени (НАЖБП) (23-66%), гепатитом С (27%), гепатитом В (32%), здоровых лиц (0-7,4%), и сравнима с таковой при ПБХ (30-84%) [3,5,9,15,21,[29][30][31]. Положительные результаты скринингового определения АNА в сыворотке крови с помощью НРИФ на криостатных срезах печени/почек/желудка крыс (мышей) в титрах ≥1:40 служат традиционным диагностическим критерием АИГ [7][8][9][10]22].…”
unclassified